Efficacy and safety of moxibustion in the treatment of cancer-related fatigue: A protocol for systematic review and meta-analysis. Issue 9 (5th March 2021) - Deng, Gen; Huang, Xianbao; Tu, Minfang; Cheng, Qinghong; Qiu, Qi; Li, Peiling; Pan, Zefeng
Abstract: Background: Cancer-related fatigue, a common symptom of cancer patients caused by the interaction of multiple factors, runs through the whole process of tumorigenesis, development, treatment, and prognosis. The main clinical manifestations are weakness, tiredness, exhaustion, fatigue, or slow movement, heavy limbs, low mood or irritability, sleep disturbance or lethargy, lack of attention, etc. CRF is different from the fatigue after daily body fatigue. It has no obvious relief or relief after rest or sleep, and exists for a long time in the relevant treatment and rehabilitation process. It seriously affects the physiological, psychological and social functions of patients, and reduces the quality of life of patients. Moxibustion therapy has shown strong advantages in the treatment of CRF, and the curative effect is accurate. Therefore, this paper will carry out a systematic evaluation and meta analysis of the efficacy and safety of moxibustion in the treatment of CRF. Methods: we will searching 8 electronic databases, including PubMed, Embase, Web of Science, Cochrane Library, the China National Knowledge Infrastructure, Chinese Science and Technology Periodical Database, Wanfang Database, and Chinese Biomedical Literature Database. We will search above electronic databases from the beginning to January 2021, without any language restriction. Clinical efficacy, including total effective rate or cure rate, clinical symptom integral, and recurrence rate will be accepted as the primary outcomes. The fatigue scale score, quality of life improvement rate will be used as secondary outcomes. RevMan 5.3 software will be used for statistical analysis. The result about the curative effect and safety of moxibustion for cancer-related fatigue will be presented as risk ratio for dichotomous data and mean differences with a 95% confidence interval for continuous data. Results: When this research program is completed, the relevant results can be obtained. Conclusions: The results of this study will provide reliable evidence for the efficacy and safety of moxibustion in the treatment of cancer-related fatigue. Ethics and dissemination: This article does not need to pass the ethics committee review, because this article does not involve the ethics question, only collates the related literature research. INPLASY Registration number: INPLASY202110072.